Differential impact of mass and targeted praziquantel delivery on schistosomiasis control in school-aged children: A systematic review and meta-analysis. - Danielle M Cribb; Naomi E Clarke; Suhail A R Doi; Susana Vaz Nery (Public Library of Science (PLoS), 2019)
Background Schistosomiasis is a widespread public health concern in the poorest regions of the world. The principal control strategy is regular praziquantel administration to school-aged children in endemic areas. With calls for the elimination of schistosomiasis as a public health problem, expanding praziquantel delivery to all community members has been advocated. This systematic review and meta-analysis compares the impact of community-wide and child-targeted praziquantel distribution on schistosomiasis prevalence and intensity in school-aged children. Methodology/principal findings We searched MEDLINE, Embase and Web of Science to identify papers that reported schistosome prevalence before and after praziquantel administration, either to children only or to all community members. Extracted data included Schistosoma species, drug administration strategy, number of treatment rounds, follow-up interval and prevalence and intensity before and after treatment. We used inverse variance weighted generalised linear models to examine the impact of mass versus targeted drug administration on prevalence reduction, and weighted boxplots to examine the impact on infection intensity reduction. This study is registered with PROSPERO, number CRD42018095377. In total, 34 articles were eligible for systematic review and 28 for meta-analysis. Schistosoma mansoni was reported in 20 studies; Schistosoma haematobium in 19 studies, and Schistosoma japonicum in two studies. Results of generalised linear models showed no detectable difference between mass and targeted treatment strategies on prevalence reduction in school-aged children for S. mansoni (odds ratio 0.47, 95%CI 0.13-1.68, p = 0.227) and S. haematobium (0.41, 95%CI 0.06-3.03, p = 0.358). Box plots also showed no apparent differences in intensity reduction between the two treatment strategies. Conclusions/significance The results of this meta-analysis do not support the hypothesis that community-wide treatment is more effective than targeted treatment at reducing schistosomiasis infections in children. This may be due to the relatively small number of included studies, insufficient treatment coverage, persistent infection hotspots and unmeasured confounders. Further field-based studies comparing mass and targeted treatment are required.